A new SVWC protein functions as a pattern recognition protein in antibacterial responses in Chinese mitten crab (Eriocheirsinensis). Issue 131 (December 2022) - Qin, Yukai; Luo, Zhi; Zhao, Ke; Nan, Xingyu; Guo, Yanan; Li, Weiwei; Wang, Qun
Abstract: Because invertebrates lack acquired immunity, they rely primarily on the innate immune system to defend themselves against viral and bacterial infections. SVWC, also called Vago, is a class of small-molecule proteins characterized by a single von Willebrand factor C-domain and appears to be restricted to arthropods. It has been reported that SVWC is involved in antiviral immunity in invertebrates, but whether it is involved in antimicrobial immunity and the mechanism of its involvement in antimicrobial immunity remains unclear. In this study, we identified a novel SVWC gene in Eriocheir sinensis and named it EsSVWC . EsSVWC was found to respond positively to bacterial stimulation and to regulate the expression of related antimicrobial peptides (AMPs). The EsSVWC protein recognized and bound to a variety of pathogen-associated molecular patterns (PAMPs) but did not exhibit direct bactericidal effects. Thus, the EsSVWC protein in crabs helps resist bacterial infection and improve survival rates. In summary, EsSVWC may regulate the innate immune system of crabs in response to microbial invasion in an indirect manner. Highlights: We identified and characterized a new SVWC gene, EsSVWC, in Eriocheir sinensis. EsSVWC regulates antimicrobial peptide expression in response to bacterial stress. EsSVWC binds to bacteria by recognizing pathogen-associated molecular patterns. EsSVWC does not have a direct bactericidal or bacterial growth inhibitory effect. EsSVWC is indirectly involved in the innate antibacterial response in E. sinensis.